Range extension of Nephasoma pellucidum, and new records of Apionsoma (Edmonsius) peclinalum (Sipuncula) and Thalassema steinbecki (Echiura) from the Pacific of Costa Rica - Dean, Harlan K.; Cutler, Edward B. (Revista de Biología Tropical, 1998)
Southern shore of Punta Morales (10° 03’ N, 84c 58’ W), Gulf of Nicoya, beneath rocks, intertidal, August I. 1996. Collector: Harlan K. Dean, four specimens (UCR-44-0 I). Islas Cortezas (10° 04 ’ N, 840 58’ W), Gulf of Nicoya, beneath rocks. intertidal, August 5, 1996. Collectors: Harlan K. Dean and Jose A. Vargas, two specimens (MCZ collection).